Bees of Florida - James Weaver; Shiala M. Naranjo; Emily Noordyke; Rachel Mallinger (EDIS)
Did you know there are over 320 species of bees in Florida and over 4,000 in the United States? Wild bees vary widely in behavior, color, size, and shape. Written by James R. Weaver, Shiala M. Naranjo, Emily Noordyke, and Rachel E. Mallinger and published by the UF/IFAS Entomology and Nematology Department, Bees of Florida is a two-page pdf guide to some common bee groups and species you may encounter in Florida. https://edis.ifas.ufl.edu/in1285